2015
DOI: 10.1177/2324709615577415
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Adenocarcinoma of Unknown Origin Presenting as Small Bowel Perforation

Abstract: Metastatic malignant tumors that originate from occult primaries are defined as “cancers of unknown origin.” We herein present the case of a 59-year-old man who presented with small bowel perforation secondary to metastatic adenocarcinoma of an unknown primary site. Imaging exhibited two pulmonary nodules, neither of which was dominant, along with mediastinal and retroperitoneal lymphadenopathy. Immunohistochemical profiling of the small bowel biopsy specimens revealed the tumor was most likely pulmonary in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…IHC for the specimen showed CK7 and TTF-1 positively which is in line with Lung Adenocarcinoma, which has been shown in several studies to be the leading type of lung cancer in small bowel metastases [3][4][5]7]; however, other studies may indicate that either squamous cell carcinoma [2,8,9] or large cell carcinoma [6,9] is more likely. This is further supported by TTF-1 having been shown to appear in 89% of metastatic lung adenocarcinoma cases and CK7 having been shown to appear in all cases of lung cancer [11]. One report indicated that large cell carcinoma has an overall 3.5 times greater rate of gastrointestinal metastasis and accounted for 30% of those metastases [6].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…IHC for the specimen showed CK7 and TTF-1 positively which is in line with Lung Adenocarcinoma, which has been shown in several studies to be the leading type of lung cancer in small bowel metastases [3][4][5]7]; however, other studies may indicate that either squamous cell carcinoma [2,8,9] or large cell carcinoma [6,9] is more likely. This is further supported by TTF-1 having been shown to appear in 89% of metastatic lung adenocarcinoma cases and CK7 having been shown to appear in all cases of lung cancer [11]. One report indicated that large cell carcinoma has an overall 3.5 times greater rate of gastrointestinal metastasis and accounted for 30% of those metastases [6].…”
Section: Discussionmentioning
confidence: 84%
“…Our patient had a post-operative course complicated with paroxysmal atrial fibrillation but otherwise was able to be discharged on postoperative day 7 and found to be doing well on a one-month outpatient followup. Survival means post-surgical intervention, in one report was six months, though those patients were specifically selected and did not have any other extrapulmonary metastasis [11]. The literature is mixed in survival rates, with some noting median rates of 2.3 months or a greater majority of patients surviving until one to three months [4,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common malignancy lesions are adenocarcinoma, neuroendocrine tumor (NET), sarcomas, and small bowel lymphoma. However, the incidence of small bowel cancer is increasing, particularly for carcinoid tumor (Islam,and series discussing small bowel tumor metastasis from lung cancer (Liu et al, 2015), cervical cancer (Qiu et al, 2015), melanoma (Conversano et al, 2014;Kouladouros et al, 2015), renal cell carcinoma (Ismail et al, 2015;Gorski et al, 2015), and unknown adenocarcinoma (Alkabie et al, 2015). On average, a small bowel cancer diagnosis is made 18 months following presentation with the first symptom.…”
Section: Introductionmentioning
confidence: 99%